Structural Study of Bis(2,6-bis(pyrazol-3-yl)pyridine)nickel(II) by Calorimetry and EXAFS Spectrometry - Kristian H. Sugiyarto (Institut Teknologi Bandung, 2004)
The stepwise complex formation of 2,6-bis(pyrazol-3-yl)pyridine, bpp, with nickel(II) perchlorate in DMF has beendetermined by calorimetric method and then followed by EXAFS spectrometry. It was found that the complexformation follows two stepwise pathways namely the formation of mono pyrazolyl-pyridine, [Ni(DMF)3 bpp]2+, andbis pyrazolyl-pyridine, [Ni(bpp)2]2+; the formation constants being log Î²1 = 6.57, and log Î²2 = 5.02, respectively,with the total value of log Î² = 11.58. The final formation of six-coordinated compound was confirmed by EXAFSanalysis with coordination number of 5.87(2) and the average of NiâNbpp bond length of 2.065(1) Ã .